Secretory structure diversity on Astronium leaf - Carneiro, Tainah Eduarda Boian [UNESP] (2022)
Astronium fraxinifolium Schott and Astronium graveolens Jacq. are included in the Anacardiaceae. The secretory structures of Anacardiaceae have been studied several times; however, there is a lack of knowledge related to these structures in Astronium, and there are inconsistencies in the taxonomy of the groups. The present study aimed to describe the internal and external secretory structures of A. fraxinifolium and A. graveolens to refine the genus’ taxonomy and highlight the uniqueness of their differentiation. Plant samples were fixed, dehydrated, and prepared for analysis by light microscopy and scanning electron microscopy using standard anatomical techniques. Non-glandular trichomes are present over the entire surface of the blade of the mature leaves of A. fraxinifolium. In contrast, in A. graveolens, non-glandular trichomes are concentrated only on the midrib region of the leaflets. The glandular trichomes, absent in the mature leaves of A. fraxinifolium, are present in the mature leaves of A. graveolens around the midrib. Astronium fraxinifolium ducts have a schizolysigenous origin, and A. graveolens have a lysigenous origin. Therefore, it was concluded that, in general, secretory structures represent a crucial taxonomic factor distinguishing these species.